Barulho danado: representações do cangaço nos jornais Diário da Manhã (PE) e Diário de Pernambuco no período lampiônico (1925-1938). - Conte, Maria Cristina Raposo (2020)
In this work, we will examine articles published in the newspapers Diario de Pernambuco and Diario da Manhã - PE, between the years 1925 and 1938, around the cangaço -species of social banditry that occurred in the Northeast of Brazil, a region lacking in social policies, which it saw in disobedience of official laws an attempt to overcome state negligence. In addition to the analysis of the primary sources, we will dialogue with texts by some historians and experts on the topic such as Frederico Pernambucano de Mello, Durval Muniz, Eric Hobsbawm and Rui Facó. In our narrative, we highlighted the figure of Lampião, now acclaimed as “the King of Cangaço”, now seen by others as one of the most cruel criminal leaders in the country, considering that the Lampionic image represents, in most cases, the very cangaço. We emphasize that our research served as a basis for the elaboration of a digital booklet, addressed to students in the 9th grade of elementary school II in the public school system. Such a booklet will contain, in addition to speeches listed in the clippings of the aforementioned newspapers, additional information, personalized illustrations and other playful attributes so that it can serve as a complement to the information brought in the textbooks.